High-Sensitivity Coil Array for Head and Neck Imaging: Technical Note - Henry, Roland G.; Fischbein, Nancy J.; Dillon, William P.; Vigneron, Daniel B.; Nelson, Sarah J. (American Journal of Neuroradiology, 2001)
Summary: The purpose of this study was to develop coils for MR imaging of the head and neck region, with the aim of improving sensitivity and coverage. A head and neck phased array coil was constructed and compared with volume and temporomandibular joint surface coils for sensitivity and coverage in phantom studies. An algorithm was implemented to correct for the nonuniformity in the surface coil reception profile. Its application to high-resolution T2-weighted imaging in healthy volunteers was investigated.